(untitled) (Advancements in Homeopathic Research, 2024)
Panic disorder is a complex condition that requires a multifaceted treatment approach. Panic disorder tends to be a chronic condition which runs an unremitting course and leads to social, occupational along with physical disability. The disorder is often associated with intense uncontrollable fear or anxiety mainly due to anticipation of threatening event. They have significant impact on the quality of life of the patient. Homoeopathy works holistically treating the patient through individualization and by taking into account mental symptoms including will, intellect, memory, emotion and physical as well as particulars. Homoeopathy cures miasmatically if any of which is persisting in the patient, reduces the use of conventional treatment and serves as a boon in patients suffering from panic disorder.